Role of Ultrasonography in the Surveillance of Disease-Free Patients with Colorectal Cancer: a Retrospective Audit - Suman, Garima (Indian J Surg Oncol, 2018)
Close surveillance of colorectal cancer (CRC) patients is helpful as early detection of resectable metastasis has a survival benefit. Ultrasonography (USG) is a frequently used modality to detect liver recurrence, although international guidelines do not include it. To evaluate the potential added role of USG in early detection of CRC recurrence. We performed a retrospective analysis of 230 patients of colorectal cancer treated at our institute in 2013–2014 who underwent abdominal USG for surveillance. 77/230 (33%) developed recurrence, with liver being the second most common site (22/230). 5/230 (2%) patients had recurrent disease first detected on USG, four of which also had raised serum CEA (carcinoembryonic antigen) levels. There were three false positive and four false-negative cases on USG. There was no added advantage of USG for early detection of CRC recurrence.